Risks of Bleeding and Stroke Based on CHA2DS2‐VASc Scores in Japanese Patients With Atrial Fibrillation: A Large‐Scale Observational Study Using Real‐World Data. Issue 5 (3rd March 2020) - Maeda, Toshiki; Nishi, Takumi; Funakoshi, Shunsuke; Tada, Kazuhiro; Tsuji, Masayoshi; Satoh, Atsushi; Kawazoe, Miki; Yoshimura, Chikara; Arima, Hisatomi
Abstract : Background: This large‐scale observational study on negative events in a real‐world setting investigated Japanese patients with atrial fibrillation who were not on anticoagulants. This study aims to evaluate the incidence of ischemic stroke and bleeding events (intracranial hemorrhage, gastrointestinal bleeding, others) based on CHA2DS2‐VASc scores in Japanese patients with atrial fibrillation who were not anticoagulated. Methods and Results: We used health checkups and insurance claim data from a Japanese insurance organization. Altogether, 9733 atrial fibrillation patients were not prescribed anticoagulation during their follow‐up periods. Patients' risk levels were defined by their CHA2DS2‐VASc scores (range 0–≥3): Men with scores of 0, 1, or ≥2 and women with scores of 1, 2, or ≥3 were considered at low, intermediate, or high risk, respectively. Cox proportional hazards model was used to assess the association between the CHA2DS2‐VASc‐determined risk and the incidence of ischemic stroke and intracranial, gastrointestinal, and other bleeding. The mean 2.5‐year follow‐up revealed 143 ischemic strokes and 332 bleeding events. Annual event rates were 0.58% for ischemic stroke and 1.17% for total bleeding events. Annual incidence of ischemic stroke increased with elevated predicted risks based on CHA2DS2‐VASc scores: 0.18% for low‐risk, 0.44% intermediate‐risk, and 1.29% high‐risk groups ( P <0.001 for trend). Annual incidences of total bleeding also increased with elevated predicted risks: 0.51% for low‐risk, 1.28% intermediate‐risk, and 2.02% high‐risk groups ( P <0.001 for trend). Conclusions: Risks of ischemic stroke and bleeding events were high, particularly among those with high CHA2DS2‐VASc scores.